La pêche artisanale en Haïti - Alaric, Jean-Paul (Expertise collective, 2021)
Subject in recent years to a number of natural disasters and political crises alike, the Republic of Haiti faces numerous developmental challenges, of which one of the foremost is food security. Small-scale fi sheries offers concrete, long-term solutions to this problem, notably through increasing the yields produced by small-scale fi sheries and aquaculture, improving the fi shery products industry, and improving the sustainable management of fi sheries resources. Within this context, The Haitian Ministry of Agriculture, Natural Resources and Rural Development has entrusted the French National Research Institute for Sustainable Development with carrying out a joint scientific assessment of the state of small-scale fisheries in Haiti. To this end, IRD has engaged a multidisciplinary committee of Haitian and French scientific and professional experts made up of agronomists, fishery experts, anthropologists, economists, geographers and environmental managers. This publication provides the latest knowledge available on small-scale fi sheries from the perspective of the environment, fi sh species and fi shery; aquaculture, ecological intensifi cation and management; and the fi shery products industry, from local level to the international context. This review of the state of existing knowledge includes more than 50 recommendations for decision-makers and fi shery stakeholders to promote the development of sustainable and equitable small-scale fi sheries in Haiti.